1985
DOI: 10.3109/00365528509089626
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Diseases and Mortality Rate

Abstract: The complications of non-tropical sprue were registered in 100 patients seen during an 18-year period. The patients had a significantly higher mortality than the age- and sex-matched general population. They had an increased incidence of malignancies, predominantly malignant lymphomas and carcinomas of the gastrointestinal tract. The disease must be considered a premalignant condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 24 publications
3
27
0
1
Order By: Relevance
“…Similar to the present study, overall SMRs were approximately 2.0 in the next 2 largest studies (conducted in United Kingdom 41 and Italy 40 ), whereas SMRs of 3.4, 3.8, and 1.0 were found in the substantially smaller investigations conducted in Denmark, 29 Italy, 42 and Finland, 25 respectively. Logan et al 41 and Corrao et al 40 described a decline in mortality risk with increasing time after diagnosis.…”
Section: Commentsupporting
confidence: 72%
See 2 more Smart Citations
“…Similar to the present study, overall SMRs were approximately 2.0 in the next 2 largest studies (conducted in United Kingdom 41 and Italy 40 ), whereas SMRs of 3.4, 3.8, and 1.0 were found in the substantially smaller investigations conducted in Denmark, 29 Italy, 42 and Finland, 25 respectively. Logan et al 41 and Corrao et al 40 described a decline in mortality risk with increasing time after diagnosis.…”
Section: Commentsupporting
confidence: 72%
“…25,[32][33][34][35][36][37] There is growing evidence that the associated serious disease outcomes linked with celiac disease could be reduced by a strict adherence to a lifelong gluten-free diet, the only effective therapy. 23,33,[38][39][40] Several generally small studies 25,29,[40][41][42] also suggest an increased overall mortality in patients with celiac disease. The Swedish Inpatient Registry provided a unique opportunity to investigate mortality risks in more than 10 000 patients with celiac disease, assess time trends throughout 30 years of follow-up, and examine long-term, cause-specific mortality outcomes, thus providing further information about the lifetime natural history of celiac disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[135][136][137] Multiple studies now support the association of CD and lymphomas. [138][139][140][141][142][143][144][145][146][147][148][149] The association between CD and intestinal T-cell non-Hodgkin lymphoma (NHL), called enteropathy-associated T-cell lymphoma (EATL), appears to be particularly strong but these aggressive lymphomas are rare. The current World Health Organization (WHO) classification of lymphomas has recommended the term enteropathy-type T-cell lymphoma (ETL).…”
Section: Lymphomamentioning
confidence: 99%
“…[100][101][102][103][104][105] Multiple studies now support the association of CD and lymphomas. [106][107][108][109][110][111][112][113][114][115][116][117][118] Patients with celiac disease have a 50-to a 100-fold increased risk of developing lymphoma compared with the general population Catassi et al in their study found that celiac disease was diagnosed in 6 (0.92%) of 653 patients with lymphoma. The odds ratio (adjusted for age and sex) for non-Hodgkin lymphoma of any primary site associated with celiac disease was 3.1 for gut lymphoma, and 19.2 for T-cell lymphoma, respectively.…”
Section: Lymphomamentioning
confidence: 99%